Exploring the Secretomes of Microbes and Microbial Communities Using Filamentous Phage Display - Gagic, Dragana; Ciric, Milica; Wen, Wesley X.; Ng, Filomena; Rakonjac, Jasna (Frontiers in Microbiology, 2016)
Microbial surface and secreted proteins (the secretome) contain a large number of proteins that interact with other microbes, host and/or environment. These proteins are exported by the coordinated activities of the protein secretion machinery present in the cell. A group of phage, called filamentous phage, have the ability to hijack the cellular protein secretion machinery in order to amplify and assemble via a secretion-like process. This ability has been harnessed in the use of filamentous phage of Escherichia coli in biotechnology applications, including screening large libraries of variants for binding to “bait” of interest, from tissues in vivo to pure proteins or even inorganic substrates. In this review we discuss the roles of secretome proteins in pathogenic and non-pathogenic bacteria and corresponding secretion pathways. We describe the basics of phage display technology and its variants applied to discovery of bacterial proteins that have functions of interest for bacterial colonization and pathogenesis, through filamentous phage display library screening. Published literature also shows that phage display is suitable for secretome protein display as a tool for identification immunogenic peptides and can be used for discovery of vaccine candidates. Secretome selection aided by next-generation sequence analysis can also be used for selective display of the secretome at a microbial community scale, the latter revealing the richness of secretome functions of interest and surprising versatility in filamentous phage display of secretome proteins from large number of Gram-negative as well as Gram-positive bacteria and archaea.